Strategic approaches to mitigating Hookworm infection: An optimal control and cost-effectiveness analysis - Z. Chazuka; C.W. Chukwu; D. Mathebula; E. Mudimu (Results in Control and Optimization)
Human hookworm infection remains a serious threat to public health, particularly in highly endemic regions. The high mortality rate associated with this infection emphasizes the urgent need for effective control measures and intervention strategies to curb its spread. A nonlinear deterministic hookworm model with saturated incidence is investigated in this paper. The model exhibits a unique disease-free and endemic equilibria, and the reproduction number is computed and explained. Sensitivity analysis shows that increasing the transmission rate, β, the hatching rate, α, the number of eggs excreted within the environment, Ne, and the rate of excretion of the eggs, γ, significantly increases the reproduction number. Based on this analysis, we extend the model to consider optimal control in the presence of three time-dependent controls namely: sanitation, preventative chemotherapy, and shoe-wearing. We define an objective function to be minimized and the conditions necessary for the optimal control are established and proved using Pontryagin’s maximum principle. We present a one-way analysis of variance to evaluate the impact of constant implementation of the control measures on the number of infected individuals. Numerical simulations also show that hookworm infection can be contained in the presence of all control measures. However, a cost-effectiveness analysis shows that combining shoe-wearing control with preventative chemotherapy is the most cost-effective measure for controlling hookworm infection. The results presented hold substantial implications for public health policy, especially in low-income regions.